2023
DOI: 10.3389/fonc.2023.1158804
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic gastrectomy for gastric cancer in patients with obesity: systematic review and meta-analysis

Abstract: IntroductionThe number of overweight patients with gastric cancer (GC) is increasing, and no previous study has compared laparoscopic gastrectomy (LG) and robotic gastrectomy (RG) in obese patients with GC. To investigate the perioperative and oncologic outcomes of RG and LG in obese GC patients, we performed a meta-analysis of propensity matched scores and retrospective studies to compare the perioperative parameters, oncologic findings, and short-term postoperative outcomes between the two groups.MethodsThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…However, none of the reviewed studies favored the laparoscopic approach over the robotic. Yu et al observed in more detail that the robotic approach was associated with a reduction in the total length of hospital stay by 0.81 days [ 8 ]. Chuan et al concluded a substantial decrease of approximately two days in the length of hospital stay with robotic gastrectomy, from -3.66 to -0.3 days, when compared to laparoscopic gastrectomy [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…However, none of the reviewed studies favored the laparoscopic approach over the robotic. Yu et al observed in more detail that the robotic approach was associated with a reduction in the total length of hospital stay by 0.81 days [ 8 ]. Chuan et al concluded a substantial decrease of approximately two days in the length of hospital stay with robotic gastrectomy, from -3.66 to -0.3 days, when compared to laparoscopic gastrectomy [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…The evaluation of time to first flatus in robotic gastrectomy versus laparoscopic gastrectomy revealed a range of findings among the 15 studies that examined it. Overall, nine out of the 15 studies reported a statistically significant decrease in time to the first flatus, in favor of the robotic approach [ 5 , 7 , 8 , 23 , 15 , 26 , 29 , 30 , 34 ]. Notably, Bobo et al [ 7 ] concluded that the time to first postoperative flatus was 0.14 days shorter for the robotic group, with Jin et al [ 29 ] and Yu et al [ 8 ] further backing up this claim (-0,105 and -0.16 days, respectively).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations